Marching to good laws: The impact of war, politics, and international credit on reforms in Ukraine - Artem Kochnev (The Vienna Institute for International Economic Studies (wiiw), 2021)
The paper investigates determinants of investments in state capacity and institutional change in contemporary Ukraine. After formulating a simple sequential two-stage model of investments in state capacity, the paper estimates autoregressive distributed lag and vector autoregressive models to verify its predictions. The paper finds little evidence for the impact of conflict intensity and access to international credit on the pace of reform progress. It finds a statistically significant effect for the intensity of political competition and changes of real wages, albeit these results are sensitive to robustness checks.
Keywords: D74; E01; E20; F51; 330; cost of war; political cycles; transition economics; Ukraine crisis; political economy; state capacity